2018
DOI: 10.1177/0264619617730860
|View full text |Cite
|
Sign up to set email alerts
|

The impact of visual impairment on nutritional status: A systematic review

Abstract: The aim of this review was to evaluate the literature that has investigated the impact of visual impairment on nutritional status. We identified relevant articles through a multi-staged systematic approach. Fourteen articles were identified as meeting the inclusion criteria. The sample size of the studies ranged from 9 to 761 participants. It was found that visual impairment significantly affects nutritional status. The studies reported that visually impaired people have an abnormal body mass index (BMI); a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
2
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 35 publications
1
31
2
4
Order By: Relevance
“…Following a systematic review of the literature (18) , a thirty-sevenquestion, cross-sectional questionnaire was designed to evaluate the impact of VI on dietary consumption, vision-related quality of life and activities of daily living (28) . The questionnaire was piloted and validated prior to the start of the study.…”
Section: Survey Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Following a systematic review of the literature (18) , a thirty-sevenquestion, cross-sectional questionnaire was designed to evaluate the impact of VI on dietary consumption, vision-related quality of life and activities of daily living (28) . The questionnaire was piloted and validated prior to the start of the study.…”
Section: Survey Designmentioning
confidence: 99%
“…Systematic review of the literature demonstrates that VI significantly impacts on nutritional status (18) . Previous studies have used a variety of methods to assess nutritional status, such as nutritional screening tools to assess whether a person is at risk of undernutrition (19) , measuring BMI (20)(21)(22) and qualitative and quantitative analysis on the ability to acquire, cook and eat food (2,(15)(16)(17)(23)(24)(25)(26) .…”
mentioning
confidence: 99%
“…Visual impairment has been shown to impact on individuals’ nutritional status (Acil & Ayaz, 2015; Baker, 2006; Bilyk, Sontrop, Chapman, Barr, & Mamer, 2009; de Faria, da Silva, & Ferreira, 2012; Gladstone et al, 2017; Gopinath, Liew, Burlutsky, & Mitchell, 2014; Jones & Bartlett, 2018; Kostyra, Zakowska-Biemans, Sniegocka, & Piotrowska, 2017; Magdalena, Urzedowicz, Motylewski, Zeman, & Pawlicki, 2016; Montero, 2005; Muurinen et al, 2014; Nakamura et al, 1999; Pardhan, Latham, Tabrett, & Timmis, 2015; Roebothan, 1999; Smyth, Spicer, & Morgese, 2014; Vági, Deé, Lelovics, & Lakatos, 2012). For example, females with sight loss are more likely to be undernourished than females without visual impairment (Muurinen et al, 2014; Stevens, Bartlett, & Cooke, 2015) and have reported being unsure about what foods they should consume for optimal eye health (Stevens et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Doctor visits and medical expenses may also contribute. Inability to carry out daily activities that reduces the quality of key lifestyle behaviors, such as socializing with others, physical activity and good diet, known to have protective effect against depression and anxiety ( Smith et al, 2017 ; Jones and Bartlett, 2018 ; López-Sánchez et al, 2019 ; Smith et al, 2019 ), may also play a big role. In addition, the ongoing and progressive nature of the underlying causes that affect vision and hearing may induce and aggravate the depressive and anxiety symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that the association between sensory impairment and mental health is bidirectional, and this could be explained by several factors associated to both sensory impairment and mental health, including difficulties with socializing ( Papadopoulos et al, 2011 ; Ritchie and Roser, 2018 ; World Health Organization, 2020a , b ), activities of daily living ( Pérès et al, 2017 ; Ritchie and Roser, 2018 ; World Health Organization, 2020a , b ), inadequate nutrition ( Jones and Bartlett, 2018 ; Ritchie and Roser, 2018 ; World Health Organization, 2020a , b ), and reduced levels of physical activity ( Ritchie and Roser, 2018 ; Smith et al, 2019 ; López-Sánchez et al, 2020b ; World Health Organization, 2020a , b ). In this study we treated difficulty seeing and hearing as the exposures and depression and anxiety as the outcomes.…”
Section: Introductionmentioning
confidence: 99%